Identification of highly conserved regulatory domains and protein-binding sites in the promoters of the rat and human genes encoding the stress-inducible 78-kilodalton glucose-regulated protein. - Resendez, E (1988)
The gene encoding GRP78 has been shown to be constitutively expressed in many cell types and is inducible by the calcium ionophore A23187. To understand the regulation of GRP78 transcription, we analyzed the components that control its basal-level expression. By transfecting deletions into cells, we have identified a 54-nucleotide cis-acting regulatory element important for high basal-level expression and a contiguous 50-nucleotide element for both basal-level expression and A23187 induction. Using DNase footprinting assays with both rat and human GRP78 promoters, we demonstrated that the protein factors present in the HeLa cell nuclear extracts bind to the regulatory regions identified by the deletion studies. This domain contains a palindromic sequence and is highly conserved among GRP genes in Caenorhabditis elegans, chicks, rats, and humans.